Grouping of Mangifera indica L. Cultivars of Subang West Java by Leaves Morphology and Anatomy Characteristics - Tri Cahyanto; Ahmad Sopian; Muhammad Efendi; Ida Kinasih (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2017)
The wide distribution and high species diversity produce large variation in morphology, anatomy and genetics of local mangoes. Until now, most mango classification system is based on the generative character while the vegetative character is neglected. Inventory of mango cultivars in Subang rarely studied, therefore the purpose of this study is to development foundation of identification methods basedthe anatomy and morphology of leavesof mango cultivars of Subang. The data could futher develop as baseline information about mango cultivar diversity in Indonesia. During study, 21 mango cultivars found in Subang, West Java. Leave samples were collected from the field and soaked in 70% alcohol. Leaf anatomy preparats made by whole-mount method and paraffin. The shape and type, location, size, density and index of stomata were observed. The results showed high similarity of all sampels.There are three variations of vascular tissues on petioles, letter U shape (planoconvex),U lobed (highlyconvex) and round (circular) with the type of drus crystal form, small cubes, and prismatic. All cultivars have actinositic stomata and hypostomatatic leaves. It could be concluded that density, size and stomata index are less powerful to be apply as characters to identified cultivars of mangoes however the presence of oxalate crystals can be use to the grouping mango cultivars in Subang.